The Impact of Digital Tax Policy and Tax Understanding on Taxpayer Compliance (Study of TikTok Affiliates in Kediri) - Ika Defiana Putri; Nur Rahmanti Ratih; M. Wahyudi (LP2M IAIN Palopo, 2026)
The development of the digital economy through social media platforms like TikTok has encouraged the emergence of affiliate marketers as a new source of income, while simultaneously creating challenges in taxation. This study aims to analyze the influence of digital tax policies and tax understanding on taxpayer compliance among TikTok affiliate marketers in Kediri City. This study used quantitative methods with a descriptive approach. Data were obtained through in-depth interviews with seven TikTok affiliate marketers, supported by observation and documentation. Data analysis was conducted using multiple linear regression analysis. The results indicate that digital tax policies and tax understanding have a positive effect on taxpayer compliance.